2021
DOI: 10.14744/bej.2021.70894
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Period of Central Corneal Thickness, Anterior Chamber Depth and Iridocorneal Angle Parameters After Deep Anterior Lamellar Keratoplasty in Keratoconus Patients

Abstract: Objectives:The purpose of this study was to assess the stabilization of anatomical outcomes of central corneal thickness (CCT), anterior chamber depth (ACD), and iridocorneal angle (ICA) in keratoconus-affected eyes after deep anterior lamellar keratoplasty (DALK). Methods: Keratoconus patients who underwent DALK surgery at Beyoğlu Eye Training and Research Hospital between January 2013 and May 2015 were retrospectively analyzed. Patients with data recorded preoperatively, 1 month postoperatively, and 1, 6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Other studies have reported visual and refractive stabilization 6 months after complete suture removal in patients who underwent DALK for keratoconus, whose refractive outcomes remained stable during a follow-up of up to 5 years. [19][20][21][22][23] However, Alvarez de Toledo et al 17 reported an initial stabilization of astigmatism after PK along the first 7 to 10 years after complete suture removal in patients with keratoconus, followed by progressive refractive and keratometric changes, with a tendency to increase myopic astigmatism, in over 50% of the patients during a followup of between 15 and 25 years. Predictability of our refractive results was similar to Lockington et al, 3 with a mean cylinder prediction error of 1.61 6 1.35 D (compared with 1.63 6 1.5 D ( 11)) and 62% of eyes within 1.5 D of the intended cylinder (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported visual and refractive stabilization 6 months after complete suture removal in patients who underwent DALK for keratoconus, whose refractive outcomes remained stable during a follow-up of up to 5 years. [19][20][21][22][23] However, Alvarez de Toledo et al 17 reported an initial stabilization of astigmatism after PK along the first 7 to 10 years after complete suture removal in patients with keratoconus, followed by progressive refractive and keratometric changes, with a tendency to increase myopic astigmatism, in over 50% of the patients during a followup of between 15 and 25 years. Predictability of our refractive results was similar to Lockington et al, 3 with a mean cylinder prediction error of 1.61 6 1.35 D (compared with 1.63 6 1.5 D ( 11)) and 62% of eyes within 1.5 D of the intended cylinder (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal transplantation has been the traditional treatment for advanced corneal diseases. It is considered the final option for patients who cannot tolerate or benefit from conservative treatments [37 ▪ ].…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…Indications for lamellar keratoplasty include contact-lens intolerant patients without significant Descemet membrane scarring from hydrops [2]. Patients should have an intact Descemet membrane for deep anterior lamellar keratoplasty (DALK), as it involves replacement of diseased corneal stroma while preserving healthy endothelium [37 ▪ ,38 ▪ ]. Because it preserves the host endothelium, DALK eliminates the risk of endothelial rejection and cell loss associated with that of penetrating keratoplasty.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…Refractive procedures should be carried out in eyes that have had prior keratoplasty once the corneal shape and refraction have stabilized. A minimum of one month should elapse between refractive surgery and all suture removal, with a three-to-six-month period following suture removal being ideal, according to several studies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%